Analysis of Intrinsic and Extrinsic Factors with the Risk of Falls in the Elderly at the Elderly Posyandu - luluk januarti; M.Hasinuddin; Alvin Abdillah (Jurnal Kesehatan dr. Soebandi, 2025)
Intrinsic,extrinsic and situational factors can help detect fall risk problems so that they can reduce the incidence of falls in the elderly. This study aims to analyze the factors associated with the risk of falling in the elderly at the Elderly Posyandu. The type of research used in this research is quantitative  research with cross-sectional method,. Respondents involved totaled 52 people, and were randomly selected using a simple random sampling technique. Data were obtained by questionnaire and analyzed using the Spearman rho statistical test and logistic regression. Results: The results of the analysis showed that intrinsic factors (movement disorders p:0.017, neurological disorders p:0.019 and visual impairments p:0.25) with the risk of falling, extrinsic factors (environmental p:0.003) with the risk of falling, situational factors (activity p: 0.031). Intrinsic factors (movement disorder OR: 324,092 and visual impairment OR: 27,240) Discussion: Intrinsic factor movement disorder is the most dominant factor associated with the risk of falling in the elderly. Further research is needed using qualitative methods to examine aspects of intrinsic factors associated with the risk of falling in the elderly.